Quality Distortion by a Discriminating Monopolist - Srinagesh, Padmanabhan; Bradburd, Ralph M. (American Economic Review, 1989)
The standard model of monopolistic imperfect quality discrimination involving consumer self-selection has shown that no distortion occurs at the highest quality level, while all lower quality levels are degraded in order to maintain profitable market segmentation. This result flows from the assumption that consumers with a higher total utility of quality also have a higher marginal utility of quality. The paper develops a reasonable model in which the standard assumption is not satisfied, and this alternative model yields vastly different conclusions regarding the form of quality distortion. In particular, quality may be enhanced, not degraded, to maintain profitable market segmentation. Copyright 1989 by American Economic Association.